Advocacy to reduce malnutrition in Uganda: Some lessons for sub-Saharan Africa - Namugumya, Brenda Shenute (International Food Policy Research Institute, 2011)
Drawing from the case of Uganda, this brief develops a model showing how advocates for improved nutrition in the countries of Sub-Saharan Africa might engage with governments and communities and move from knowledge to commitment to action in order to sharply reduce the numbers of the malnourished. The focus here is on the use of advocacy to foster sustainable partnerships and implement nutrition strategies in Sub-Saharan Africa.